Delayed differentiation practices on supply chain management- a theoretical review / Mohd. Fauzi Mohd Harun ... [et al.] - Mohd Harun, Mohd. Fauzi; Md Taib, Ridzuan; A Tambi, Abdul Malek; Idris, Noraini; Mohd Hanafiah, Mohd Hafiz; Abd Razak, Farrah Dina; Laidin, Jamilah (2012)
The literature investigates the importance of delayed differentiation on supply chain management. Its application was found in the 1920's (Yang and Burn, 2003). The literature traced the symptom of study by referring to the seminal work of Alderson (1950). Alderson argued that overall costs could be reduced by postponing a differentiating stage of production. The classical work was then extended by viewing it as an opportunity to shift the risk of owning goods from one position in a supply chain to another. Later researcher as depicted in the theory matrix perceived delayed or postponement differentiation as labeling, packaging, assembly, manufacturing and time. This perception of postponement continues in part to this day. The theory matrix also depicted the evolution of research from single activities to clustering of activities. The reconceptualization of delayed differentiation identified gaps in existing literature. Van Hoek (2001) issued five challenges for future delayed differentiation that will capture its dynamics and improve the methodological robustness of the concept. Hence after Van Hoeks more robust analysis such as Structured Equation Modeling was used to measure relationship between variables and construct. Such analysis will bring the dynamics of the research. <ewer suggestion to accommodate changes of research question such as qualitative approach to be used to answer some of the research question was also identified leading to theory building as oppose to the more traditional approach of theory testing. Thus, multiple of data collection that encompasses within case study, ethnography may find way in supply chain management research. The conceptual framework suggested sustainability of business performance is pertinent as literatures pointed out the move towards strategy as part of configuring the supply chain activities with the industry structure.